Integrasi Manajemen Sumber Daya Manusia dan Budaya Kepemimpinan dalam Penguatan Tanggung Jawab Sosial Perusahaan di Era Transformasi Digital: Studi Kasus Klik Madura - Abadi, Rifqi Setiawan (re-JIEM (Research Journal of Islamic Education Management), 2026)
This study is motivated by the importance of strengthening corporate social responsibility in the era of digital transformation through the integration of human resource management and leadership culture within organizations. The research question addressed is how this integration is achieved and its implications for organizational sustainability. This study aims to analyze the forms of integration and their impact on organizational practices. It employs a qualitative approach using a case study design through interviews, observations, and documentation. The findings indicate that integration is achieved through social-value-based recruitment, competency development emphasizing ethics and individual responsibility, and participatory leadership that encourages employee engagement in social activities. This integration strengthens the implementation of corporate social responsibility, enhances employee commitment, and supports organizational sustainability in the digital era. This study provides theoretical and practical contributions to organizations in integrating human resource management and leadership culture.